Detection of Parechovirus and Enterovirus Among Infants Evaluated for Late-onset Sepsis in the Neonatal Intensive Care Unit: The Viral Respiratory Infections in the Neonatal Intensive Care Unit-Parechovirus-Enterovirus Study. Issue 12 (14th September 2022) - Sánchez, Pablo J.; Woods, Reginald A.; Wang, Huanyu; Ronchi, Andrea; Pietrasanta, Carlo; Michelow, Ian C.; Mosca, Fabio; Pugni, Lorenza; Leber, Amy
Abstract : In a prospective cohort study of 65 inborn infants who were evaluated for late-onset sepsis at >72 hours of age in 2 academic neonatal intensive care units, none had parechovirus or enterovirus RNA detected by polymerase chain reaction performed on nasopharyngeal specimens during the first or subsequent sepsis evaluations (n = 80).